DESIGN AND DEVELOPMENT OF ACCOUNTING INFORMATION SYSTEM FOR CASH SALES OF MILD STEEL - Ari Puspita; Yuyun Yuningsih; Muhammad Fahmi; Rahmat Tri Yunandar (Jurnal Riset Informatika, 2021)
Abstract Technological developments are now experiencing rapid growth, so many entrepreneurs compete to produce new companies. At this time, the light steel business is multiplying. The researcher tries to research the weak steel sales system. Most companies do not have a computerized recording system, so inputting invoices is hampered. Sales notes are written manually to report generation, so that it will take a long time. In making the information system, the author will use the waterfall model and will use the PHP programming language for the manufacture of this software. The purpose of making this sales information system is to make it easier to carry out a mild steel sales system to shorten processing time and minimize all forms of errors in reporting.